Social Risks and Challenges of the Post-Socialist Transition Period in Estonia: Analysis of Biographical Narratives - Grishakova, Marina; Margarita, Kazjulja (Qualitative Sociology Review, 2008)
In research on social risks and insecurity qualitative methods have obvious advantages and successfully complement statistical quantitative approaches, which have been practiced for decades. This study is based on the thirty-two in-depth interviews collected in the period June 2003 to January 2004 for the project “Life Plans and Life Paths in the Post-Socialist Estonia.” The interviewees are representatives of the so-called “generation of winners”, i.e. the people aged 20 or 30 years at the beginning of the period of post-socialist reforms. The paper examines representations of social risks and challenges of the transition period in the biographical interviews as well as discursive patterns and strategies that interviewees use to produce relatively coherent biographical narratives